New insights and reaction mechanisms on ZrO2 (110) surface enhanced catalytic hydrolysis of CFC-12: a density functional theory study - Zheng, Dalong; Song, Xin (Journal of molecular modeling, 2024)
Context Freon, a greenhouse gas that contributes to the depletion of the ozone layer, has been the subject of investigation in this study. The catalytic hydrolysis enhancement of CFC-12 by ZrO 2 was examined using a density functional theory approach. A detailed reaction mechanism and a new reaction pathway were proposed. The study found that CFC-12 is more likely to be adsorbed on the ZrO 2 surface in the CFC-12-T O (F) configuration, while H 2 O is more likely to be adsorbed on the ZrO 2 surface in the H 2 O-T O (H) configuration. Additionally, H 2 O replaces CFC-12 on the surface of ZrO 2 . The hydrolysis of CFC-12 is primarily determined by the first dechlorination process, while the defluorination process is comparatively easier. ZrO 2 has a catalytic effect on both dechlorination and defluorination processes, with a more pronounced effect on the former. The production of C–OH bonds is inhibited, which facilitates the dechlorination and defluoridation processes. Methods This work was carried out in the Dmol 3 program in the Material Studio 2017, including the geometric structure optimization and energy calculations. The GGA/PBE method was used in this work, along with the DNP basis, spin-polarized set, and DFT-D correction. The possible TSs were guessed based on the linear synchronous transit/quadratic synchronous transit/conjugate gradient (LST/QST/CG) method, and they were further confirmed and reoptimized to ensure that the only one imaginary frequency exists in the TSs.